Credit Constraints, Political Instability, and Capital Accumulation - Herrala, Risto (IMF Working Papers; Working Paper, 2013)
We investigate the complex interactions between credit constraints, political instability, and capital accumulation using a novel approach based on Kiyotaki and Moore's (1997) theoretical framework. Drawing on a unique firm-level data set from Middle-East and North Africa (MENA), empirical findings point to a large and significant effect of credit conditions on capital accumulation and suggest that continued political unrest worsens credit constraints. The results support the view that financial development measured by a relaxing of financial constraints is key to macroeconomic development.